Fibroblast activation protein and the tumour microenvironment: challenges and therapeutic opportunities - Lee, Hsing Hwa; Al-Ogaili, Zeyad (Oncology Reviews, 2025)
Fibroblast Activation Protein (FAP) has emerged as a critical player in cancer biology, particularly in shaping the tumour microenvironment (TME) and influencing immunotherapy outcomes. FAP-positive cancer-associated fibroblasts (CAFs) play multiple roles in tumour progression and immune modulation. FAP, predominantly expressed on CAFs, contributes significantly to extracellular matrix remodelling, angiogenesis, and the creation of an immunosuppressive milieu. There are complex interactions between FAP-positive CAFs and various components of the immune system, highlighting their impact on T cell function and macrophage polarisation. This makes FAP a promising target for cancer therapy and potentially as a biomarker for immunotherapy treatment response. This review highlights the clinical challenges to target FAP and also addresses the heterogeneity of CAFs with the need for more refined characterisation to enhance therapeutic strategies and future research directions.